التشويق والترغيب في حسن التخلص إلى خاتمة القصيدة: قصائد مختارات من الشعر الأندلسي عصر ملوك الطوائف - البياتي، ياسر رشيد حمد (جامعة تكريت - كلية الآداب, 2016)
تناول البحث موضوعا مهما من مواضيع اللغة العربية لا سيما في مجال الأدب والشعر على وجه الخصوص؛ وهو موضوع (حسن التخلص) إلى خاتمة القصيدة، وهذا الموضوع يبين للقارئ مدى تمكن الشاعر من أدواته اللغوية، إذ أن القصيدة تكون كلا كاملا تأتي مترابطة الأجزاء مكتملة تنصب من مصب واحد، وهذا الترابط يكون كله عن طريق حسن التخلص وتمكن الشاعر منه، ولهذا الموضع أساليب يعتمد عليها الشعراء ومنها (التشويق والترغيب)، وهذا ما وقفنا عليه في بحثنا هذا وقد جاء البحث على مبحثين: الأول: مفهوم التخلص (حسن التخلص). الثاني: (التشويق والاستدراك) في حسن التخلص إلى خاتمة القصيدة في الشعر الأندلسي. ومن ثم خاتمة حاول البحث أن يوجز الفكرة فيها فكرة البحث بمجمله.
The research an important topic of the Arabic language, especially in the field of literature and poetry in particular; a subject (Hassan disposal) to the conclusion of the poem, the subject shows the reader the degree to which the poet of linguistic tools, as the poem is both fully come interconnected incomplete portions focus the mouth of one, and this interdependence is all through the good and get rid of it enables the poet, but this place methods relied upon poets, including (thrill and carrots), and this is what we stand for in our present research came on two themes: First: the concept of the disposal (Hassan disposal). II: (thrill of being aware) in Hassan disposed to the conclusion of the poem in the Andalusian poetry. And then try searching epilogue that summarizes idea where the idea of research as a whole.
Keywords: الشعر العربي -- الدواوين والقصائد -- نقد الشعر -- الأندلس -- عصر ملوك الطوائف